Prognostic relevance of tumor response after neoadjuvant therapy for patients with esophageal cancer - Bollschweiler, Elfriede; Hölscher, Arnulf H. (Annals of Translational Medicine, 2019)
In recent years, pre and perioperative chemotherapy or chemoradiotherapy have been successfully implemented for advanced esophageal carcinoma (1,2). Traditionally, the resected specimen and lymph nodes (LN) have been evaluated according to the Union for International Cancer Control (UICC)/TNM system. The gold standard for evaluation of the of the prognosis after surgical therapy is the pathological TNM (pTNM) staging system. UICC established the 7th edition of the TNM system for esophageal cancer in 2009 (3). This was followed in 2018 by the current 8th edition (4,5).